Murine models to study human NK cells in human solid tumors - Parodi, Monica; Astigiano, Simonetta; Carrega, Paolo; Pietra, Gabriella; Vitale, Chiara; Damele, Laura; Grottoli, Melania; Guevara Lopez, Maria de la Luz; Ferracini, Riccardo; Bertolini, Giulia; Roato, Ilaria; Vitale, Massimo; et al. (Frontiers in Immunology, 2023)
Since the first studies, the mouse models have provided crucial support for the most important discoveries on NK cells, on their development, function, and circulation within normal and tumor tissues. Murine tumor models were initially set to study murine NK cells, then, ever more sophisticated human-in-mice models have been developed to investigate the behaviour of human NK cells and minimize the interferences from the murine environment. This review presents an overview of the models that have been used along time to study NK cells, focusing on the most popular NOG and NSG models, which work as recipients for the preparation of human-in-mice tumor models, the study of transferred human NK cells, and the evaluation of various enhancers of human NK cell function, including cytokines and chimeric molecules. Finally, an overview of the next generation humanized mice is also provided along with a discussion on how traditional and innovative in-vivo and in-vitro approaches could be integrated to optimize effective pre-clinical studies.